Site selection and traverse planning to support a lunar polar rover mission: A case study at Haworth Crater. (October 2016) - Heldmann, Jennifer L.; Colaprete, Anthony; Elphic, Richard C.; Bussey, Ben; McGovern, Andrew; Beyer, Ross; Lees, David; Deans, Matt
Abstract: Studies of lunar polar volatile deposits are of interest for scientific purposes to understand the nature and evolution of the volatiles, and also for exploration reasons as a possible in situ resource to enable long term human exploration and settlement of the Moon. Both theoretical and observational studies have suggested that significant quantities of volatiles exist in the polar regions, although the lateral and horizontal distribution remains unknown at the km scale and finer resolution. A lunar polar rover mission is required to further characterize the distribution, quantity, and character of lunar polar volatile deposits at these higher spatial resolutions. Here we present a case study for NASA's Resource Prospector (RP) mission concept for a lunar polar rover and utilize this mission architecture and associated constraints to evaluate whether a suitable landing site exists to support an RP flight mission. We evaluate the landing site criteria to characterize the Haworth Crater region in terms of expected hydrogen abundance, surface topography, and prevalence of shadowed regions, as well as solar illumination and direct to Earth communications as a function of time to develop a notional rover traverse plan that addresses both science and engineering requirements. We also present lessons-learned regarding lunar traverse path planning focusing on the critical nature of landing site selection, the influence of illumination patterns on traverse planning, the effects of performing shadowed rover operations, the influence of communications coverage on traverse plan development, and strategic planning to maximize rover lifetime and science at end of mission. Here we present a detailed traverse path scenario for a lunar polar volatiles rover mission and find that the particular site north of Haworth Crater studied here is suitable for further characterization of polar volatile deposits.